Pengaruh Event Marketing, Konsep Perumahan Dan Lokasi Terhadap Keputusan Pembelian Rumah Pada PT. Bhumi Inti Propertindo Singaraja - Ni Luh Yuni Nilam; Puspita Dewi; Gede Widyadnyana Pasek (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study was to determine the impact of event marketing, housing concepts and location on home purchase decisions at Bhumi Inti Propertindo Singaraja. The examination procedure used in this research is validity and reliability test, classical assumption test, multiple linear regression analysis, t-test, analysis of determination and f-test test. The results of the review show that the promotion mix influences the decision to purchase a house at Bhumi Inti Propertindo Singaraja. From the test results with the T test, it shows that event marketing has a significant effect on home buying decisions. The housing concept influences the decision to buy a house at Bhumi Inti Propertindo Singaraja. From the test results with the T test shows that the concept of housing affects the decision to buy a house. Location has a direct effect on home purchase decisions at Bhumi Inti Propertindo Singaraja. From the test results with the T test shows that the location affects the decision to buy a house. Judging from the f-test, it is found that the F-count > F-table is 212,297 > 3.12, this shows that event marketing, housing concepts and location basically affect the decision to buy a house with a sig level. big. 0.000 < 0.050. Keywords : event marketing, housing concept, location, home buying decisions